2008
DOI: 10.1016/j.jbiomech.2007.10.013
|View full text |Cite
|
Sign up to set email alerts
|

In situ friction measurement on murine cartilage by atomic force microscopy

Abstract: Articular cartilage provides a low-friction, wear-resistant surface for the motion of diarthrodial joints. The objective of this study was to develop a method for in situ friction measurement of murine cartilage using a colloidal probe attached to the cantilever of an atomic force microscope. Sliding friction was measured between a chemically functionalized microsphere and the cartilage of the murine femoral head. Friction was measured at normal loads ranging incrementally from 20 to 100 nN with a sliding spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
55
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 56 publications
15
55
3
Order By: Relevance
“…Measured ECM moduli were greater than those previously reported for the superficial zone (154 kPa versus 44 kPa) of porcine patellar cartilage [66] and the middle/deep zone (90 -106 kPa versus 81 kPa) of porcine articular cartilage [38]. Furthermore, the observed ECM microscale elastic properties decreased with depth from the articular surface.…”
Section: Discussioncontrasting
confidence: 62%
“…Measured ECM moduli were greater than those previously reported for the superficial zone (154 kPa versus 44 kPa) of porcine patellar cartilage [66] and the middle/deep zone (90 -106 kPa versus 81 kPa) of porcine articular cartilage [38]. Furthermore, the observed ECM microscale elastic properties decreased with depth from the articular surface.…”
Section: Discussioncontrasting
confidence: 62%
“…7,44,45 We hypothesize that this relative softness lends itself toward a plowing mechanism that contributed to the observed friction values. 52 TGFb enhances SZP secretion in SZ articular chondrocytes 14,26,27 and may provide an avenue to concomitantly improve mechanical and frictional properties.…”
Section: Figmentioning
confidence: 99%
“…Atomic Force Microscopy (AFM) has been widely used to identify frictional properties of various materials and the role of boundary lubricants at the microscopic level by measuring the surface roughness and the frictional coefficient [21][22][23][24]. Kim et al [25] reported that the friction of a soft contact lens surface was significantly reduced under the lubrication of saline solution, whereas Liu and Bhushan found that using perfluoropolyether (PFPE) as a lubricant could significantly improve the frictional behavior of a silicon surface [26].…”
Section: Introductionmentioning
confidence: 99%